Dāwūd al-Muqammaṣ in njegovo razumevanje krščanskega nauka = Dāwūd al-Muqammaṣ and His Reception of Christian Doctrine - Krajnc, Aljaž (2021)
After the emergence of Islam in the early seventh century, the Arabic language saw its rapid expansion and eventually become a theological language as well. Non-Muslim theo-logians living in the Islamic world began to express themselves in Arabic and wrote polemical literature against their adversaries from different religions and religious denominations. Of special importance were also Jewish theologians who wanted to demonstrate the correct-ness of their own religious beliefs and the ill-foundedness of Christian and Muslim doctrines. This paper is dedicated to the Arabic speaking Jewish theologian Dāwūd al-Muqammaṣ (the 9th century A.D.), whose work Twenty Chapters (ʿIšrūn maqāla) is the earliest extant summa theologiae in Arabic, i.e., a work which aims to address the totality of theological teachings of a certain religion. The eight chapter of this work contains a critique of the Christian doc-trine that God is three, while the tenth chapter refutes the Christian teachings that the Son is from eternity begotten by the Father and that God was incarnated in reality. This paper places Dāwūd’s critique in the broader context of trans-confessional polemic in the medieval Islamic world with special attention to Judeo-Arabic tradition.
Keywords: Dāwūd al-Muqammaṣ; Judeo-Arabic tradition; Judaism; critique of Christianity; Kalām; Religious Polemics